Gonad-infecting species of Philometra (Nematoda: Philometridae) from groupers Epinephelus spp. (Osteichthyes: Serranidae) in the Bay of Bengal, India - Moravec, František; Manoharan, Jayaraman (Acta parasitologica, 2014)
Based on light and scanning electron microscopical studies, two new and one specifically not identified gonad-infecting species of Philometra Costa, 1845 (Nematoda: Philometridae) are described from the ovary of marine fishes of the genus Epinephelus Bloch (Serranidae, Perciformes) in the Bay of Bengal, off the eastern coast of India: P. indica sp. nov. (male and females) from the honeycomb grouper E. merra Bloch, P. tropica sp. nov. (males and females) from the duskytail grouper E. bleekeri (Vaillant) and Philometra sp. (only females) from the cloudy grouper E. erythrurus (Valenciennes). Philometra indica is mainly characterized by the length of spicules 192-195 μm and the gubernaculum 84 μm, the distal tip of the gubernaculum without a dorsal protuberance, and by the presence of five pairs of caudal papillae. Philometra tropica is mainly characterized by the spicules conspicuously ventrally distended at their posterior halves, the distal tip of the gubernaculum with a dorsal protuberance, and the presence of three pairs of caudal papillae.
Keywords: hlístice; druhová specificita; Male; Fish Diseases; Nematoda; Bays; zátoky; Indie; mužské pohlaví; Species Specificity; India; ryby; Fishes; Animals; ženské pohlaví; nematodózy; zvířata; nemoci ryb; Nematode Infections; Female